Comparing nebulized water versus saline after laryngeal desiccation challenge in Sjögren's Syndrome. (14th May 2013) - Tanner, Kristine; Roy, Nelson; Merrill, Ray M.; Kendall, Katherine; Miller, Karla L.; Clegg, Daniel O.; Heller, Amanda; Houtz, Daniel R.; Elstad, Mark
Abstract : Objectives/Hypothesis: This study examined the effects of a laryngeal desiccation challenge and two nebulized hydration treatments on phonation threshold pressure (PTP), vocal effort, and throat dryness in patients with chronic airway dryness. Study Design: Double‐blind, within‐subjects crossover design. Methods: Eleven individuals with Primary Sjögren's Syndrome received a 15‐minute laryngeal desiccation challenge (breathing dry air–<1% relative humidity–transorally), followed by nebulized isotonic saline or nebulized water treatments (3 mL) on 2 consecutive weeks. PTP, as well as self‐perceived vocal effort, mouth, and throat dryness were assessed before and after the desiccation challenge, and at 5, 35, and 65 minutes after the nebulized treatment. Results: The laryngeal desiccation challenge produced statistically significant increases in PTP, vocal effort, and mouth and throat dryness ( P  < 0.05). Nebulized saline produced greater—but not statistically significant—treatment effects than water. PTP was more correlated with throat dryness than vocal effort. Conclusion: Patients with chronic airway dryness experienced phonatory changes following dry air exposure. Nebulized isotonic saline may offset this effect. Future research should explore dose‐response relationships among dry air exposure, nebulized treatments, voice change, and self‐perceived throat dryness. Level of Evidence: 1b. Laryngoscope, 123:2787–2792, 2013